RESPON TANAMAN JAGUNG VARIETAS LOKAL NTT UMUR SANGAT GENJAH (PENA TUNUâ€™ ANAâ€™) TERHADAP CEKAMAN KEKERINGANÂ - Murningsih, Tri; Yulita, Kusumadewi Sri; Bora, Charles Y.; Arsa, I.G.B. Adwita (BERITA BIOLOGI, 2015)
In dry land areas such as Nusa Tenggara Timur (NTT), low production of maize may due to selection of using local varieties that are mostly drought tolerant.One of the local varieties known as Pena Tunu? Ana? have been harversted in very early age of 1.5 month, hence it was categorised as very early mature maize. This variety is therefore play an important role in the food security system for people in NTT as they can be harvested earlier than other varieties. However, no information has yet on how this variety response to drought stress. Drought stress is one of the factors causing the decline in maize production. This study was conducted at experimental house in Cibinong Science Centre (CSC) to evaluate responses of Pena Tunu? Ana? against drought stress treatment. The experiment was done in six degree of drought treatments, 0 (control), 4, 8, 12, 16 and 20 days with 4 replications. Parameters measured were soil water, relative leaf water,proline and sugar content in leaves and roots at each level of drought stressed. Results showed that with increasing level of drought stress,soil water and relative leaf water content were decreased while proline and sugar content were increased. At the same level of drought stress, accumulation of proline and sugar in the roots was higher than those in the leaves. Drought stress terminated at 16 days, where the roots content of proline reached 10.36 mg/g and sugar 110.91 mg/g, while the leaves content of proline was of 2.84 mg/g and sugar was of 38.44 mg/g. At the level of drought stress during 16 days, the plants suffered temporary wilting but refreshed after watering.